A Survey of Executive Coaching Practices in New Zealand - Ian Brooks; Sarah Wright (International Journal of Evidence Based Coaching and Mentoring, 2007)
Executive coaching is a rapidly growing form of organisation development intervention, and one which is receiving increasing attention in the management and psychology literature. This study reports on the state of the practice of executive coaching in New Zealand, about which little is currently known. Fifty-nine executive coaches responded to a survey that gathered data on the demographics of coaches; their backgrounds, qualifications and training; their coaching method; and aspects of their practice, including typical fees charged, number of client sessions, method of marketing, ethical standards and professional insurance. Conclusions are drawn from the data and suggestions for future research are made.